FEATURES OF THE PHENOTYPE AND NAD(P)-DEPENDENT DEHYDROGENASES ACTIVITY IN NEUTROPHIL BY PATIENTS WITH WIDESPREAD PURULENT PERITONITIS IN PROGNOSIS FOR SEPSIS DEVELOPMENT - А. А. Savchenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The aim of the study was to examine the features of phenotype and the levels of NAD(P)-dependent dehydrogenases activity of blood neutrophils in the prognosis of abdominal sepsis development in patients with widespread purulent peritonitis (WPP). 50 patients with WPP of community and hospital origin in the pre-operative period were examined. From the 5th to the 10th day of the postoperative period 35 patients (70%) had developed abdominal sepsis, 15 patients (30%) had absence of complications. As controls 67 respect healthy people were examined. The research blood neutrophils phenotype was performed by f low cytometry using a direct immunofluorescence whole peripheral blood. The levels of surface receptor expression was assessed by the mean fluorescence intensity. The NAD(P)-dependent dehydrogenases activity in the blood neutrophils studied using bioluminescence method. It was established that the inflammatory reaction in patients with WPP is characterized by neutrophilia and changes in the phenotype of blood neutrophils. The markers of the subsequent development of sepsis in WPP are less pronounced (in comparison with the indices of uncomplicated patients), an increase in the number of neutrophils, a decrease in the HLA-DR + -cell count against the background of a high level of neutrophils expressing a high affinity receptor for IgG. The patients without subsequent complications had the number of neutrophils with CD23 receptor expression is increased. Metabolism of neutrophils in patients with WPP is characterized by a decrease in the intensity of plastic processes due to low activity of glucose-6-phosphate dehydrogenase and an imbalance in the activity of the enzymes of the mitochondrial compartment. A feature of the neutrophil metabolism in patients with WPP without subsequent development of sepsis is a high activity of anaerobic lactate dehydrogenase reaction and a decrease in the activity of NADP-dependent decarboxylating malate dehydrogenase. The patients with WPP with subsequent development of sepsis had a high level of NAD-dependent out flow of substrates from the tricarboxylic acid cycle on the amino acid exchange reaction via glutamate dehydrogenase which can affect the activity of aerobic respiration of blood neutrophils. The established differences in the phenotype and activity of enzymes in the blood neutrophils in patients with WPP depending on the subsequent development of sepsis determine the possibility of creating a method for predicting the development of complications and developing immunoactive therapy in the postoperative period of WPP.